Monitoring cardiorespiratory fitness in professional soccer players: Is it worth the prick? - Buchheit, M.; Simpson, B. M.; Lacome, M. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To compare between-tests changes in submaximal exercise heart rate (HRex, 3 min, 12 km/h) and the speed associated with 4 mmol/L of blood lactate (V4mmol) in soccer players to get insight into their level of agreement and respective sensitivity to changes in players` fitness. Methods: A total of 19 elite professional players (23 [3] y) performed 2 to 3 graded incremental treadmill tests (3-min stages interspersed with 1 min of passive recovery, starting speed 8 km/h, increment 2 km/h until exhaustion or 18 km/h if exhaustion was not reached before) over 1.5 seasons. The correlation between the changes in HRex and V4mmol was examined. Individual changes in the 2 variables were compared (>2 × typical error considered "clear"). Results: The changes in HRex and V4mmol were largely correlated (r = .82; 90% confidence interval, .65-.91). In more than 90% of the cases, when a clear individual change in HRex was observed, it was associated with a similar clear change in V4mmol (the same direction, improvement, or impairment of fitness) and conversely. Conclusions: When it comes to testing players submaximally, the present results suggest that practitioners can use HRex or V4mmol interchangeably with confidence. However, in comparison with a field-based standardized warm-up run (3-4 min, all players together), the value of a multistage incremental test with repeated blood lactate samplings is questionable for a monitoring purpose given its time, labor, cost, and poorer player buy-in.